Analisis Kesulitan Belajar Akademik Siswa-Siswi SMAN 13 Surabaya - Amrih Dwi Wulandari; Sabilah, Rosyadatus; Muhammad Latif Fatkurrohman; Aula Rahma Putri; Likfatmawati Maslakah; Kaniati Amalia (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
Academic learning difficulties are a challenge that is often found and faced by students when studying at school and at home. Internal factors such as motivation, ability, cognitive, and there are external factors such as family environment, teacher teaching methods, learning facilities and also teacher support are also important to determine the success of student learning. This study aims to analyze various forms of students' academic learning difficulties at school and at home, as well as understand the influence of the environment on the success of students' learning. This study uses a qualitative descriptive approach. Data collection techniques include in-depth interviews with teachers and questionnaires involving students, observations are carried out in the school environment of  SMAN 13 SURABAYA. The results of the study showed that students of SMAN 13 SURABAYA had diverse learning disabilities, learning difficulties that were felt included students having difficulty concentrating, sleepiness during lunch, teachers who lacked in explaining material and unconducive classroom conditions. In the questionnaire data that I got, most of the students had difficulty in understanding the subjects of Mathematics, Physics, English and Chemistry. This can affect the academic performance of students. The academic learning difficulties of SMAN 13 Surabaya students are caused by the interaction between internal and external factors. To overcome learning difficulties in students, efforts can be made such as strengthening learning strategies by teachers, improving learning facilities, and active involvement of parents in supporting the learning process of students.